2019
DOI: 10.1038/s41598-019-54113-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in and significance of platelet function and parameters in Kawasaki disease

Abstract: Kawasaki disease (KD) is a systemic febrile, inflammatory vascular disease of unknown etiology. The coronary artery abnormality (CAA) caused by KD has become the most commonly acquired heart disease in children. Initial treatment of intravenous immunoglobulin (IVIG) can reduce the incidence of CAA. Thrombocytosis is common during the course of KD, but changes in and significances of platelet function and parameters are unclear. In this study, we enrolled 120 patients, including 40 patients with KD, 40 febrile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…An increase in PLT count in children with KD is usually associated with exacerbation of inflammation [ 23 ]. Therefore, the present study examined the altered levels of cytokines in patients treated with or without clopidogrel during IVIG therapy.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in PLT count in children with KD is usually associated with exacerbation of inflammation [ 23 ]. Therefore, the present study examined the altered levels of cytokines in patients treated with or without clopidogrel during IVIG therapy.…”
Section: Resultsmentioning
confidence: 99%
“…More significantly, despite the decreased incidence of virus infection in group 2 compared with group 1, the same frequency of IVIG response and CALs or nCALs was observed, which could imply a loose association between IVIG resistance, CALs and concurrent virus infection in patients with KD [ 27 ]. Prior studies also indicated that coronary artery abnormality (and the response to IVIG) in the children with KD may be related to the extent of inflammation (such as greater CRP), not to whatever pathogen is present [ 29 31 ]. In addition, during laboratory testing, the increased value of neutrophil percentage differing from that of the past 5 years, could be associated with the higher ratio of concurrent MP infection.…”
Section: Discussionmentioning
confidence: 99%
“…Initial treatment of intravenous immunoglobulin (IVIG) can reduce the incidence of CAL. 31 However, some children with KD show complete nonresponse or only a partial response to IVIG. These children may have immune tolerance to this treatment.…”
Section: Features Of Ikdmentioning
confidence: 99%